2020
DOI: 10.3390/children7120279
|View full text |Cite
|
Sign up to set email alerts
|

Video Modeling and Social Skills Learning in ASD-HF

Abstract: Autism spectrum disorders represent a heterogeneous group of clinical situations, and are mainly represented by a deficit of social communication. In this study, we compare two strategies to enhance communicative/social skills, namely self-video modeling and peer video modeling. The subjects were divided into two groups treated via the method of self-video modeling (group 1) or peer video modeling (group 2). For both groups of subjects affected by ASD-HF (Autism Spectrum Disorder-high-functioning), three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…Such technology-based interventions include video modeling (e.g., recording videos of the self or a peer to later watch and perform) and virtual reality techniques (e.g., interactive situation-based learning opportunities). One study found that modeling based on recorded self-recordings was associated with faster acquisition of affect recognition and empathic responses skills compared to peer-video recording modeling [ 48 ]. Preliminary studies have found this method was effective in teaching children to recognize and label emotions, even in nonverbal participants [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such technology-based interventions include video modeling (e.g., recording videos of the self or a peer to later watch and perform) and virtual reality techniques (e.g., interactive situation-based learning opportunities). One study found that modeling based on recorded self-recordings was associated with faster acquisition of affect recognition and empathic responses skills compared to peer-video recording modeling [ 48 ]. Preliminary studies have found this method was effective in teaching children to recognize and label emotions, even in nonverbal participants [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the patients with level 1 ASD, several studies proved a significant impairment in social cognition abilities ( 36 38 ). Our study confirmed lower performances in ER and ToM compared with the TD group (76% of children and adolescents with ASD scored under 2 standard deviations in ER and 82% in ToM).…”
Section: Discussionmentioning
confidence: 99%
“…Mentor Video mucul sebagai contoh pemodelan dalam perkembangan media sosial dalam melesatnya kemajuan teknologi. Tidak seperti Video Modelling yang mengunakan sebuah video contoh yang memberikan gambaran perilaku untuk ditiru dalam pelatihan (DiGennaro Reed dkk., 2023) yang juga sudah banyak diaplikasikan untuk pengajaran murid yang berkebutuhan khusus seperti autisme dalam membaca (Egarr & Storey, 2022), STEM (Wright et al, 2020),dan kemampuan sosial (Alhuzimi, 2022;Frolli et al, 2020;Petursdottir & Gudmundsdottir, 2023); konsep Mentor Video dalam penelitian ini lebih ke penggunaan contoh video sebagai standar acuan dalam pengembangan konten.…”
Section: Pendahuluanunclassified